Proposal for the EU CAP compliant agricultural budgeting model in Montenegro - Gordana DJUROVIC; Branko BULATOVIC (Agricultural Economics (AGRICECON), 2014)
After the official start of the Montenegrin accession negotiations with the EU in June 2012, it is important to plan a significant increase in the agricultural budget financing well ahead of the accession. Considering the structure and economic importance of agriculture for the generation of Montenegrin GDP, the balanced trade deficit, the reduction of poverty and the regional disparities in development and reversing the negative demographic trends, the proposed reformed agricultural budget of Montenegro in the period 2014-2018 outlines significantly higher levels of the funding both as a share of the state budget and the GDP. The proposed proportions of financing of the key measure groups in the subsequent tables utilize as a starting point the model defined in the Montenegrin National Program of Food Production and Rural Development 2009-2013. Some changes in the proportion of the measures are also proposed according to the agricultural sector needs and the institutional capacity building for the next phase of the EU accession negotiations. In order to prepare the Montenegrin agriculture to cope with the competitive pressures of the EU single market, the indisputable conclusion of this study is that the proposed future levels of agricultural funding in the agricultural budget should be at least near to those (in the relative terms) of the comparable economies of the Western Balkans countries.